Cost‐effective and Facile Production of a Phosphorus‐doped Graphite Electrode for the Electrochemical Determination of Pyridoxine. Issue 6 (6th April 2021) - Dokur, Ebrar; Gorduk, Ozge; Sahin, Yucel
Abstract: In this study; a sensitive, selective, and simple electrochemical sensor was developed to determine low concentration pyridoxine (Py) using a phosphorus‐doped pencil graphite electrode (P‐doped/PGE). Electrode modification was implemented using the chronoamperometry method at +2.0 V constant potential and 100 seconds in 0.1 mol L −1 H3 PO4 supporting electrolyte solution. The characterization processes of the P‐doped/PGE were carried out using electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV), X‐ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FESEM), energy‐dispersive X‐ray spectroscopy (EDX), and atomic force microscope (AFM) methods. In the concentration study, using the differential pulse voltammetry (DPV) method, a linear calibration plot was acquired in the concentration range of 0.5 to 300 μmol L −1 Py. The limit of quantification (LOQ) and limit of detection (LOD) of the developed method were calculated as 0.219 μmol L −1 and 0.0656 μmol L −1, respectively. Detection of Py has been successfully performed on the P‐doped/PGE in the beverage samples. As a result, the method developed has been shown to have fast, low cost, and simple for the sensitive and selective detection of Py as an effective electrode. Abstract :